FOREIGN EXCHANGE ALLOCATION AND ECONOMIC GROWTH IN NIGERIA: A SECTORAL ANALYSIS - Oji Greatness Udo; Udokang Nsisong Boniface (Scholar Express Journals, 2021)
The study empirically examined foreign exchange allocations and economic growth in Nigeria spanning from the period of 1985 to 2018. In other to ascertain the nature of relationship that exist between the construct of the study, secondary data sourced from Central bank of Nigeria Statistical Bulletin was employed. The unit root test was employed to ascertain the level of stationarity of the data. Additionally, the Johansen cointegration test was employed to ascertain whether there is long run association between the predictor and the criterion variables. From the result of the Ordinary Least Square (OLS) correction model test, an insignificant and positive relationship exist between foreign exchange allocation to agricultural and industrial sectors and economic growth in Nigeria. While an insignificant and negative relationship exist between oil sector and gross domestic product in Nigeria. Additionally, an insignificant and positive relationship exist between service sector, transportation sector and gross domestic product in Nigeria. From the result of the granger causality test, no directional causality existed between the dependent variable and the independent variables. Therefore, the study recommends that government should support economic growth using other policies other than foreign exchange allocation and government needs to encourage trading of foreign currencies in the economy in order to boost economic growth in Nigeria
Keywords: Foreign exchange allocation; Economic growth; Agriculture; Manufacturing